2012
DOI: 10.3390/jfb3040706
|View full text |Cite
|
Sign up to set email alerts
|

Cytocompatibility and Mechanical Properties of Short Phosphate Glass Fibre Reinforced Polylactic Acid (PLA) Composites: Effect of Coupling Agent Mediated Interface

Abstract: In this study three chemical agents Amino-propyl-triethoxy-silane (APS), sorbitol ended PLA oligomer (SPLA) and Hexamethylene diisocyanate (HDI) were identified to be used as coupling agents to react with the phosphate glass fibre (PGF) reinforcement and the polylactic acid (PLA) polymer matrix of the composite. Composites were prepared with short chopped strand fibres (l = 20 mm, ϕ = 20 µm) in a random arrangement within PLA matrix. Improved, initial composite flexural strength (~20 MPa) was observed for APS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Another desirable attracting property in materials for fixation devices is the ability to absorb energy during fracture. helped retain mechanical properties for a long period since hydrolysis at interface was delayed [35].…”
Section: Tablementioning
confidence: 99%
“…Another desirable attracting property in materials for fixation devices is the ability to absorb energy during fracture. helped retain mechanical properties for a long period since hydrolysis at interface was delayed [35].…”
Section: Tablementioning
confidence: 99%
“…Only in the case of significant increase in anisotropy, an increase in E is suspected to occur when the diameter of metaphosphate fibers decreases 43,44 . While, the tensile strength and Young's modulus of the investigated fibers are similar to those reported for other bioactive phosphate glass fibers, while having a larger diameter, 18,22‐24,45 the change in the Young's modulus with decreasing the fiber diameter cannot, at present, be explained. Possible assumptions include (a) the slipping of the large fibers in the grip which would lead to an underestimation of the Young's modulus and/or (b) the aging (and water retention) of the fibers.…”
Section: Discussionmentioning
confidence: 52%
“…A large number of studies were reported on phosphate glasses and fibers for medical applications from invert phosphate glasses 17,18 that cannot be drawn into fibers to metaphosphate glasses/fibers 19 . Ahmed et al evidenced that the addition of boron oxide or iron oxide into the phosphate network can lead to fibers with higher tensile strength and Weibull modulus than the silica‐based bioactive fibers 20‐24 . With regards to application in biosensing, Sglavo et al developed calcium phosphate fibers and capillaries with tensile strength of 200‐350 MPa and Weibull modulus ranging from 3 to 6 25 .…”
Section: Introductionmentioning
confidence: 99%
“…The composite obtained was compatible with MC3T3-E1 murine pre-osteoblast cell line. The P45 phosphate glass fiber-reinforced PLA composites investigated by Hasan MS et al 26 who also demonstrated cytocompatibility with the human MG63 cell line.…”
Section: Introductionmentioning
confidence: 97%